2021
DOI: 10.17645/up.v6i3.4274
|View full text |Cite
|
Sign up to set email alerts
|

Variable Arrangements Between Residential and Productive Activities: Conceiving Mixed-Use for Urban Development in Brussels

Abstract: Mixing productive economic activities with housing is a hot topic in academic and policy discourses on the redevelopment of large cities today. Mixed-use is proposed to reduce adverse effects of modernist planning such as single-use zoning, traffic congestion, and loss of quality in public space. Moreover, productive city discourses plead for the re-integration of industry and manufacturing in the urban tissue. Often, historical examples of successful mixed-use in urban areas serve as a guiding image, with ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Sehingga dari keragaman fungsi tersebut menghasilkan kawasan pergudangan tersebut menjadi sesuatu yang lebih baik dan menjadi daya tarik baru bagi kota tersebut. Dampak positif dari penggunaan konsep pengembangan penggunaan campuran tersebut juga terjadi di Kota Brussel yang diteliti oleh Ryckewaert et al (2021) yang mengemukakan bahwa dengan penggunaan konsep pengembangan "live-work" yang terbatas untuk kawasan permukiman dan aktivitas produktif maka sesuai dengan tujuan perencanaan tata ruang yang valid akan berhasil mendapatkan esensi "good neighbours" dan "tolerance" dari pencampuran kedua kegiatan tersebut. Penelitian ini bertujuan untuk mengevaluasi konsep pembangunan kawasan campuran Taman Bisnis CIBIS, apakah sudah memenuhi kriteria karakteristik kawasan campuran khususnya kriteria keanekaragaman penggunaan (diversity of use) dan kriteria desain (design).…”
Section: Sejarah Artikelunclassified
“…Sehingga dari keragaman fungsi tersebut menghasilkan kawasan pergudangan tersebut menjadi sesuatu yang lebih baik dan menjadi daya tarik baru bagi kota tersebut. Dampak positif dari penggunaan konsep pengembangan penggunaan campuran tersebut juga terjadi di Kota Brussel yang diteliti oleh Ryckewaert et al (2021) yang mengemukakan bahwa dengan penggunaan konsep pengembangan "live-work" yang terbatas untuk kawasan permukiman dan aktivitas produktif maka sesuai dengan tujuan perencanaan tata ruang yang valid akan berhasil mendapatkan esensi "good neighbours" dan "tolerance" dari pencampuran kedua kegiatan tersebut. Penelitian ini bertujuan untuk mengevaluasi konsep pembangunan kawasan campuran Taman Bisnis CIBIS, apakah sudah memenuhi kriteria karakteristik kawasan campuran khususnya kriteria keanekaragaman penggunaan (diversity of use) dan kriteria desain (design).…”
Section: Sejarah Artikelunclassified
“…These principles also shaped the suburban context across Europe and North America. Other studies have identified, investigated or mentioned similar post-industrial landscapes in Belgium, Italy, Germany, Great Britain, and the USA [14,[21][22][23][24][25]. Given that YILs cover vast expanses of land-up to 25% of the total area in some Danish suburbs-our understanding of these landscapes is astonishingly limited [15,26].…”
Section: Young Industrial Landscapes and Their Transformation Potentialmentioning
confidence: 99%
“…According to the experience of western developed countries and the development of my country, since the reform and opening-up policies are introduced, the process of rapid urbanization is usually accompanied by the transformation of urban spatial form and the intensification of various conflicts within the society. It has been found that it is quite common for the quality of urban public life to deteriorate due to improperly designed physical spaces [20].…”
Section: Related Workmentioning
confidence: 99%